2001
DOI: 10.1034/j.1399-3054.2001.1130202.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of glutathione in adaptation and signalling during chilling and cold acclimation in plants

Abstract: Glutathione is an important component of the ascorbate-glutathione cycle, which is involved in the regulation of hydrogen peroxide (H2O2) concentrations in plants. During chilling and cold acclimation, i.e. exposure to temperatures between 0 and 15 degrees C, H2O2 may accumulate. Excess electrons from the photosynthetic and respiratory electron transport chains can be used for the reduction of oxygen, thus producing superoxide radicals (O2.-); these are subsequently transformed to H2O2 via superoxide dismutase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(136 citation statements)
references
References 57 publications
7
127
0
2
Order By: Relevance
“…In AGB002 the increase of O 2 − radicals was 102% compared to control plants on day 7 of the experiment whereas, in AGB025, O 2 − increased by 140% compared to control plants. It was interesting to observe the correlation between O 2 • − and MDA concentration in AGB025 which was in agreement with the previous studies of Kocsy et al (1997Kocsy et al ( , 2001,). The reduction in peroxidation and cell viability towards the end of the cold exposure observed in AGB002 may be due to the better antioxidant enzyme machinery.…”
Section: Cell Damage and Oxidative Stresssupporting
confidence: 80%
See 3 more Smart Citations
“…In AGB002 the increase of O 2 − radicals was 102% compared to control plants on day 7 of the experiment whereas, in AGB025, O 2 − increased by 140% compared to control plants. It was interesting to observe the correlation between O 2 • − and MDA concentration in AGB025 which was in agreement with the previous studies of Kocsy et al (1997Kocsy et al ( , 2001,). The reduction in peroxidation and cell viability towards the end of the cold exposure observed in AGB002 may be due to the better antioxidant enzyme machinery.…”
Section: Cell Damage and Oxidative Stresssupporting
confidence: 80%
“…2c and d). The increased activity and expression of antioxidant enzymes and levels of antioxidant molecules in W. somnifera and other plant species under various stresses has also been reported earlier (Kocsy et al, 1996(Kocsy et al, , 2001Jaleel et al, 2008Jaleel et al, , 2009Kaur et al, 2012;Sabir et al, 2012;Mishra et al, 2014). The combined action of CAT and SOD converts the O 2− and H 2 O 2 to water and O 2 , thus, prevent the cellular damage under unfavorable condition (Arora et al, 2014).…”
Section: Antioxidant Enzymesmentioning
confidence: 89%
See 2 more Smart Citations
“…Both AsA and GSH are required in plants to maintain the intergrity of the photosynthetic membranes and an active AsA-GSH pathway under oxidative stress. 30,31,32 In addition, Kocsy et al 33 suggested that the change of AsA/DHA and GSH/GSSG was more important in cell resistance against ROS compared with AsA or GSH content. Under salt stress decline in AsA/DHA and GSH/GSSG ratios was reversed by SA application.…”
Section: Discussionmentioning
confidence: 99%